Production of three-dimensional tissue-engineered cartilage through mutual fusion of chondrocyte pellets. Issue 9 (September 2016) - Hoshi, K.; Fujihara, Y.; Mori, Y.; Asawa, Y.; Kanazawa, S.; Nishizawa, S.; Misawa, M.; Numano, T.; Inoue, H.; Sakamoto, T.; Watanabe, M.; Komura, M.; et al.
Abstract: In this study, the mutual fusion of chondrocyte pellets was promoted in order to produce large-sized tissue-engineered cartilage with a three-dimensional (3D) shape. Five pellets of human auricular chondrocytes were first prepared, which were then incubated in an agarose mold. After 3 weeks of culture in matrix production-promoting medium under 5.78 g/cm 2 compression, the tissue-engineered cartilage showed a sufficient mechanical strength. To confirm the usefulness of these methods, a transplantation experiment was performed using beagles. Tissue-engineered cartilage prepared with 50 pellets of beagle chondrocytes was transplanted subcutaneously into the cell-donor dog for 2 months. The tissue-engineered cartilage of the beagles maintained a rod-like shape, even after harvest. Histology showed fair cartilage regeneration. Furthermore, 20 pellets were made and placed on a beta-tricalcium phosphate prism, and this was then incubated within the agarose mold for 3 weeks. The construct was transplanted into a bone/cartilage defect in the cell-donor beagle. After 2 months, bone and cartilage regeneration was identified on micro-computed tomography and magnetic resonance imaging. This approach involving the fusion of small pellets into a large structure enabled the production of 3D tissue-engineered cartilage that was close to physiological cartilage tissue in property, without conventional polyper scaffolds.